Conventional inactivated bivalent H5/H7 vaccine prevents viral localization in muscles of turkeys infected experimentally with low pathogenic avian influenza and highly pathogenic avian influenza H7N1 isolates - Toffan, Anna (Taylor & Francis, 2008)
Highly pathogenic avian influenza (HPAI) viruses cause viraemia and systemic infections with virus replication in internal organs and muscles; in contrast, low pathogenicity avian influenza (LPAI) viruses produce mild infections with low mortality rates and local virus replication. There is little available information on the ability of LPAI viruses to cause viraemia or on the presence of avian influenza viruses in general in the muscles of infected turkeys. The aim of the present study was to determine the ability of LPAI and HPAI H7N1 viruses to reach muscle tissues following experimental infection and to determine the efficacy of vaccination in preventing viraemia and meat localization. The potential of infective muscle tissue to act as a source of infection for susceptible turkeys by mimicking the practice of swill-feeding was also investigated. The HPAI virus was isolated from blood and muscle tissues of all unvaccinated turkeys; LPAI could be isolated only from blood of one bird and could be detected only by reverse transcriptasepolymerase chain reaction in muscles. In contrast, no viable virus or viral RNA could be detected in muscles of vaccinated/challenged turkeys, indicating that viral localization in muscle tissue is prevented in vaccinated birds.